Stakeholders’ awareness and perception of food design in the Netherlands - Hendrik N. J. Schifferstein (International Journal of Food Design)
The first designers specialized in food design in the Netherlands about 25 years ago. Since then, more and more designers have joined them and presented their work at exhibitions and events. In addition, specialized food design courses and curricula have been developed. However, interviews with professionals and scientists in the field of nutrition and public health show that the term food design is still largely unknown and often interpreted negatively, pointing to how food marketing manipulates consumers and seduces them into buying unhealthy products. Nevertheless, participants see opportunities for designers to support healthy and sustainable food choices by presenting them in a more attractive way or in more prominent locations. In addition, designers could improve food or optimize its packaging, improve nutrition education, redesign food environments and facilitate collaboration between stakeholders to achieve systemic change. However, to create impact, the public should better understand what food design is and how it can contribute, and designers should demonstrate that their interventions are effective.